The SOD Gene Family in Tomato: Identification, Phylogenetic Relationships, and Expression Patterns - Feng, Kun; Yu, Jiahong; Cheng, Yuan; Ruan, Meiying; Wang, Rongqing; Ye, Qingjing; Zhou, Guozhi; Li, Zhimiao; Yao, Zhuping; Yang, Yuejian; Zheng, Qingsong; Wan, Hongjian (Frontiers in Plant Science, 2016)
Superoxide dismutases (SODs) are critical antioxidant enzymes that protect organisms from reactive oxygen species (ROS) caused by adverse conditions, and have been widely found in the cytoplasm, chloroplasts, and mitochondria of eukaryotic and prokaryotic cells. Tomato (Solanum lycopersicum L.) is an important economic crop and is cultivated worldwide. However, abiotic and biotic stresses severely hinder growth and development of the plant, which affects the production and quality of the crop. To reveal the potential roles of SOD genes under various stresses, we performed a systematic analysis of the tomato SOD gene family and analyzed the expression patterns of SlSOD genes in response to abiotic stresses at the whole-genome level. The characteristics of the SlSOD gene family were determined by analyzing gene structure, conserved motifs, chromosomal distribution, phylogenetic relationships, and expression patterns. We determined that there are at least nine SOD genes in tomato, including four Cu/ZnSODs, three FeSODs, and one MnSOD, and they are unevenly distributed on 12 chromosomes. Phylogenetic analyses of SOD genes from tomato and other plant species were separated into two groups with a high bootstrap value, indicating that these SOD genes were present before the monocot-dicot split. Additionally, many cis-elements that respond to different stresses were found in the promoters of nine SlSOD genes. Gene expression analysis based on RNA-seq data showed that most genes were expressed in all tested tissues, with the exception of SlSOD6 and SlSOD8, which were only expressed in young fruits. Microarray data analysis showed that most members of the SlSOD gene family were altered under salt- and drought-stress conditions. This genome-wide analysis of SlSOD genes helps to clarify the function of SlSOD genes under different stress conditions and provides information to aid in further understanding the evolutionary relationships of SOD genes in plants.